Cardiovascular complications in end stage renal disease in a tertiary hospital in Nepal - Panjiyar, Rajesh; Sharma, Rajeev; Laudari, Shankar; Gupta, Madhu; Ghimire, Madhav; Subedi, Pawina; Subramanyam, Gagnapatnam (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The cardiovascular complications including morbidity and mortality remains alarmingly high in all stages of chronic kidney disease. Although patients with chronic kidney disease share many of the similar risk factors for cardiovascular disease as the general population, there are a number of uremia related risk factors, such as anemia and alterations in calcium/phosphorus metabolism that also play a role in promoting cardiovascular disease. The objective of the study was to study the cardiovascular complications in end stage renal disease patients on maintenance hemodialysis. Materials & Methods: It is a hospital based cross-sectional observational study conducted at College of Medical Science - teaching Hospital. Hundred patients (n=100) with a diagnosis of end stage renal disease (irrespective of the underlying cause), and those who were on hemodialysis support were studied over a period of one year. Results: One hundred end stage renal disease patients were analyzed. Cardiovascular disease was present in 74% (n=74). the mean age of the patient who had cardiovascular disease was 59.36+14.337 years. The three major causes of end stage renal disease in the study population were hypertension (35%) followed by diabetes(31%) and chronic glomerulonephritis (14%). On electrocardiogram, left ventricular hypertrophy was a major finding 64% (n=64) followed by arrhythmias 30% (n=30). On echocardiography, left ventricular hypertrophy was found in 49% (n=49) followed by left ventricular diastolic dysfunction 38% (n=38). On subgroup analysis, left ventricular hypertrophy was found statistically significant with calcium and phosphorus product > 55 mg2/dl2 (p=0.01). Similarly left ventricular systolic dysfunction, regional wall motion abnormalities and st-t changes was found statistically significant with anemia; p=0.006, p=0.0004 and p=0.02 respectively. Conclusion: Prevalence of cardiovascular complications were common in end stage renal disease patients receiving maintenance hemodialysis. Anemia, calcium and phosphorus product > 55 mg2/dl2 were their independent risk factors.